2022
DOI: 10.1002/nag.3341
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of single pile settlement based on stress bubble fictitious soil pile model

Abstract: Taking both pile end stress diffusion effect and pile-soil interface softening effect into account, a new nonlinear method for the vertical settlement of pile is proposed in this paper. In detail, a new model, namely stress bubble fictitious soil pile model, is proposed to simulate the support from the pile bottom soil. The nonlinear soil softening model is introduced to establish the relationship between unit pile shaft friction and pile-soil relative displacement. Then, a nonlinear calculation method for loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The earth beneath the pile foundation compresses and deforms due to the external load of the pile foundation, creating settlement, and the ultimate settlement S may be described as follows [31]:…”
Section: Soil Compression Settlementmentioning
confidence: 99%
“…The earth beneath the pile foundation compresses and deforms due to the external load of the pile foundation, creating settlement, and the ultimate settlement S may be described as follows [31]:…”
Section: Soil Compression Settlementmentioning
confidence: 99%
“…According to the layered characteristics of the PES and whether there is sediment or compaction at the pile end, FSP can be divided into several sections along the vertical direction; that is, the layered characteristics of the PES can be considered in the FSP model. In recent years, the FSP model was also utilized to study the torsional vibration and settlement problems of pile foundation [22,29,[41][42][43][44][45]. However, to popularize the model in engineering, the FSP model needs to be applied to more engineering cases to verify its rationality.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted by El Naggar and Wei [1,2], as well as Ghazavi and Ahmadi [3], showed that the horizontal and axial bearing capacities of TPs increased by 77% and 80%, respectively, compared with those of a CP with the same length and volume. The static bearing characteristics of TPs have been thoroughly investigated by many researchers [4][5][6][7][8]. In addition to bearing static loads, the TP is also often subjected to dynamic loadings arising from traffic, wind, waves, machine vibrations and seismic loadings, etc.…”
Section: Introductionmentioning
confidence: 99%